Novel Twig Sampling Method by Unmanned Aerial Vehicle (UAV) - Käslin, Florian; Baur, Thomas; Meier, Philip; Koller, Patrick; Buchmann, Nina; D'Odorico, Petra; Eugster, Werner (Frontiers in Forests and Global Change, 2018)
Biophysical and biochemical traits of foliage and twigs at the top of tree canopies provide essential information on trees’ ecophysiology. Conventional methods used for canopy sampling are typically time consuming and costly, while the very canopy tops are still out of reach unless a canopy crane is used. Thus, we developed a novel twig sampling method using a device attached to a drone that allows to grasp and cut small twigs and bring them to the ground for immediate analysis. This ``Flying Tree Top Sampler'' (FTTS) complements existing methods used in tree canopy research. This paper describes the method to make it openly available to interested users, provides the necessary technical details, and reports on a proof-of-concept application by probing a single tree during senescence. In this demonstration example we show that the ability to investigate the top part of the tree leads to the clear finding that chlorophyll content of the top leaves is significantly lower than that of leaves in the lower canopy. Without the samples collected by the FTTS, the decrease of chlorophyll content with height would not have been of statistical significance using a p = 0.05 significance threshold. Besides its advantages, the existing limitations of the FTTS are discussed, and suggestions for future developments are provided.